Synthesis and Characterization of Calcium Phosphate-Based Material Containing P and K Based on Acetylene Gas Waste Raw Material Using Dissolution and Precipitation Methods - Apprinda Wahyudyah Winali; Srie Muljani; Suprihatin Suprihatin; Ely Kurniati; Citra Siwi Estiningtyas (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
Acetylene gas waste possesses considerable potential for reutilization because of its high calcium content, although inadequate management may lead to adverse environmental effects. This research was conducted to synthesize and characterize multinutrient phosphate-based materials derived from acetylene gas waste through dissolution and precipitation techniques. The synthesis involved reacting calcium hydroxide obtained from acetylene gas waste with phosphoric acid (H?PO?), followed by a precipitation process using NH?OH and KOH solutions. The experimental variables included pH values ranging from 7 to 11 and H?PO? concentrations between 15% and 55%. Characterization of the synthesized products was performed using X-Ray Fluorescence (XRF), Scanning Electron Microscopy (SEM), and X-Ray Diffraction (XRD) to evaluate elemental composition, crystal morphology, and crystalline structures. The findings revealed that higher pH values and increased H?PO? concentrations had a significant influence on both the yield and quality of the precipitated products. The maximum yield of 90% was achieved at an H?PO? concentration of 55% and pH 10. SEM observations revealed that the products exhibited a finer, more homogeneous crystal morphology, while XRF analysis confirmed that calcium was the dominant element, accompanied by phosphorus and potassium, indicating the successful synthesis of calcium phosphate-based materials. Furthermore, XRD analysis confirmed the formation of crystalline calcium phosphate compounds. Overall, the study highlights the potential application of acetylene gas waste as an alternative raw material for the production of sustainable and environmentally friendly phosphate fertilizers. Contribution to Sustainable Development Goals (SDGs):SDG 9: Industry, Innovation and InfrastructureSDG 12: Responsible Consumption and ProductionSDG 13: Climate Action